Tra2 protein biology and mechanisms of splicing control. (11th August 2014) - Best, Andrew; Dalgliesh, Caroline; Kheirollahi-Kouhestani, Mahsa; Danilenko, Marina; Ehrmann, Ingrid; Tyson-Capper, Alison; Elliott, David J.
Abstract : Tra2 proteins regulate pre-mRNA splicing in vertebrates and invertebrates, and are involved in important processes ranging from brain development in mice to sex determination in fruitflies. In structure Tra2 proteins contain two RS domains (domains enriched in arginine and serine residues) flanking a central RRM (RNA recognition motif). Understanding the mechanisms of how Tra2 proteins work to control splicing is one of the key requirements to understand their biology. In the present article, we review what is known about how Tra2 proteins regulate splicing decisions in mammals and fruitflies.